Analysis of the Content of Communication Messages by Tiktok Video Content on Vina Muliana's Account in Entering the World of Work - Kana Rizky Ramadhani; Faridah Faridah (Jurnal Pamator : Jurnal Ilmiah Universitas Trunojoyo, 2023)
Vina Muliana, the owner of the TikTok account @vmuliana, discusses the world of work, whether it's discussing tips on applying for a job or personal branding. The purpose of this research is to analyze the content of the message and find out what communication techniques he uses in the process of delivering the message content that he uploads in video content on his TikTok account with the @vmuliana account. This research method uses qualitative methods with descriptive explanations. The data used in this study refers to the focus on video content uploaded to the @vmuliana account; the last video documentation that was examined was the video on Saturday, March 18, 2023. Video documentation for uploaded content will be taken following the theme of the discussion of the communication techniques used so that it has a more straightforward explanation and has the effectiveness of the explanations and examples carried out in the uploaded video content. References from Discourse Analysis assist instruments in message content analysis research. It can be seen that the TikTok account @vmuliana uses four communication strategy techniques that aim to make the message she conveys in the delivery process easy to understand and acceptable to the public. The four communication strategy techniques are redundancy (repetition), canalizing, informative, educative, persuasive, and coercive. The explanation has been explained along with the sentences she uses following the communication strategy techniques she uses to deliver the message.